Crisis management tool in the assessment of financial stability - O. B. Repkina; D. O. Konovalova (Путеводитель предпринимателя, 2020)
Economic crises forced to re-evaluate the needfor and the importance of crisis management in the modern national economy. Crisis management is not only a mandatory event in the management of the company under bankruptcy, but also a component of the enterprise management system, the main aim of which is to prevent or eliminate financial instability in a cyclical economic development.